Short taxonomic review of little-known Phaneropterinae (Orthoptera: Tettigoniidae) from Malay Peninsula - Tan, Ming Kai (Zootaxa, 2014)
The taxonomy of three genera of little-known Phaneropterinae from Malay Peninsula (Singapore and Peninsular Malaysia) is reviewed: Cesasundana Koçak & Kemal, 2009, Elbenia Stål, 1876 and Macedna Karsch, 1891. One new species each from the genera Cesasundana and Elbenia are described from Singapore and Peninsular Malaysia respectively: Cesasundana lorniensis sp. n. and Elbenia fraser sp. n. Keys to species of Cesasundana and Elbenia are also included. The taxonomic position of monotypic genus Macedna is validated, male is redescribed and the female is described for the first time.